ARYLSALFATASE ACTIVITY IN MARINE POLYCHAETES - DHEVENDARAN, K (Fishery Technology, 2017)
Marine polychaetes, collected from the Vellar Estuary exhibited arylsulfatase activity. Lumbriconeries sp. Polydora sp. M onojis sp. and H eteromastus sp. were selected for this study. Of these, Heteromastus sp. showed maximum enzymatic activity and it has been chosen for the enzyme kinetic studies such as pH, optimal temperature, period of incubation and the effect of DDT. Enzyme activity showed single peak at pH 6.2possibly indicating the presence of one type of arylsulfatase. Maxim.'Jm activity was attained after 12 h of incubation at 29Â°C. DDT has an inhibiting effect on the arylsulfatase activity even at the concentration of 10 p.p.m. and the activity was completely lost at 100 p.p.m.